Contemporary Evolution in CRISPR–CAS9 System Technology and their Uses in Treatment of Human Common Diseases: A Review (Medico Legal Update, 2021)
Gene therapy has proven its potential in treatment of several human diseases. Most recent method in a longline of the genome-editing-techniques is called “A Clustered-Regularly-Interspaced-Short-PalindromicRepeat-associated-protein9” abbreviated as CRISPR-Cas9. The scientists and researcher have long soughtto the control, and modification the DNA that consider “the code of life”. The CRISPR-Cas9technology isoffer very important improvements that differ about other gene-editing.technologies, it’s uncomplicated toapply & low-cost, also have comparatively high degree of the efficiency and precision . This technologyuses a “.ribonucleic acid.(RNA)-guided. Deoxyribonucleic. acid-DNA-endonuclease.”, Cas9, whichinduces double-strand breaks (DSBs) in the target site, the DSBs was repaired by the use of a variety ofcellular DNA-repair systems leading to changes in target sites, that technology have proven to be effectiveto investigation, prevention, and treatment of diseases.This review summarizes contemporary evolution in CRISPR –Cas9 system technology and their uses intreatment of common diseases.